INTEGRATION ZONE DEVELOPMENT IN BUREAUCRATIC REFORM - Tiyas Nur Haryani; Apriana Puspasari (Universitas Sebelas Maret, 2020)
Bureaucracy in Indonesia can be said as not optimal yet, so that there is still massive increase in corruption crime rate. Therefore, government conducts bureaucratic reform to reduce corruption practice. This research aimed to describe the implementation of bureaucratic reform in the attempt of suppressing corruption crime rate occurring in the organization of government in Indonesia. Analysis was conducted using library study providing descriptive qualitative data. Considering the data obtained from library study, it could be seen that Ministry of State Apparatuses Empowerment and Bureaucratic Reform has issued integrity zone policy in realizing corruption-free region (WBK)/ clean, catering-on bureaucratic region (WBBM).There are some important points in integrity zone development: change management, management arrangement, human resource management arrangement, accountability reinforcement, and public service quality improvement. Integrity zone policy is expected to give implication to the reduced corruption crime in government organization